An efficient hydrogen evolution catalyst composed of palladium phosphorous sulphide (PdP∼0.33S∼1.67) and twin nanocrystal Zn0.5Cd0.5S solid solution with both homo- and hetero-junctions. Issue 1 (8th December 2016) - Song, Jingang; Zhao, Haitao; Sun, Ranran; Li, Xiyou; Sun, Dejun
Abstract : The combination of both homo- and hetero-junctions in one catalyst can significantly improve the catalytic activity for H2 evolution from water. Abstract : Zn x Cd1− x S solid solutions have been successfully demonstrated as excellent visible light responsive catalysts for hydrogen evolution from water in the presence of sacrificial reagents. Especially Zn0.5 Cd0.5 S with a twin crystal structure is the best pristine sulphide catalyst ever reported so far due to the presence of the homo-junctions between the zinc blende (ZB) and wurtzite (WZ) segments, which improved the separation of the photon generated electron–hole pairs. However, a further improvement in the catalytic activities of the twin crystal Zn0.5 Cd0.5 S solid solution has never been reported. In the present work, palladium phosphorous sulphide (PdP∼0.33 S∼1.67 ) was used for the first time as a co-catalyst and found that the photocatalytic H2 production rate and efficiency of the twin nanocrystal Zn0.5 Cd0.5 S solid solution in the presence of acidic or alkaline sacrificial reagents were significantly enhanced. The H2 production rates of Zn0.5 Cd0.5 S/PdP∼0.33 S∼1.67 under visible light illumination ( λ > 420 nm) in 0.75 M ascorbic acid (pH = 2.39) and 0.7 M Na2 S/0.5 M Na2 SO3 (pH = 13.86) aqueous solutions are measured to be 372.12 μmol h −1 mg −1 and 246.04 μmol h −1 mg −1, respectively, which are 67 and 5.8 times higher than those of pristine twinned Zn0.5 Cd0.5 S solid solution. Moreover, the H2 production rate of 372.12 μmol h −1 mg −1 is the highest value ever reported so far for sulphide photocatalysts in the presence of acidic sacrificial reagents. The examination on the morphology of the Zn0.5 Cd0.5 S/PdP∼0.33 S∼1.67 hybrid catalyst using SEM, TEM and HRTEM techniques revealed the presence of hetero-junctions between the deposited PdP∼0.33 S∼1.67 and Zn0.5 Cd0.5 S phases, as well as homo-junctions between the ZB and WZ phases in this hybrid catalyst. The synergistic effects of homo- and hetero-junctions on the separation of the generated electron–hole pairs are responsible for the significantly promoted catalytic activities of the hybrid catalyst. This result suggests that combination of both homo- and hetero-junctions in one catalyst is a promising strategy for improving the catalytic activities of sulphide catalysts for hydrogen evolution from water.